Spatial and socioeconomic inequities in liveability in Australia's 21 largest cities: Does city size matter?. (November 2022) - Giles-Corti, Billie; Saghapour, Tayebeh; Turrell, Gavin; Gunn, Lucy; Both, Alan; Lowe, Melanie; Rozek, Julianna; Roberts, Rebecca; Hooper, Paula; Butt, Andrew; Higgs, Carl
Abstract: Spatial and area-level socioeconomic variation in urban liveability (access to social infrastructure, public transport, open space, healthy food choices, local employment, street connectivity, dwelling density, and housing affordability) was examined and mapped across 39, 967 residential statistical areas in Australia's metropolitan (n = 7) and largest regional cities (n = 14). Urban liveability varied spatially, with inner-city areas more liveable than outer suburbs. Disadvantaged areas in larger metropolitan cities were less liveable than advantaged areas, but this pattern was reversed in smaller cities. Local data could inform policies to redress inequities, including those designed to avoid disadvantage being suburbanised as cities grow and gentrify. Highlights: Greater efforts are needed to avoid widening health inequities as cities grow and gentrify. Outer suburban areas are poorly served by local amenity and infrastructure. This may not always equate with socioeconomic inequities, depending upon a city's size. Urban policies are needed to avoid the suburbanisation of disadvantage into low density low-liveable areas. Local data is essential to inform decision-making and investments to ensure liveability for all.